Transnational organised crime in international law - Obokata, Tom (Studies in international and comparative criminal law, 2010)
A monograph that offers a critical analysis of developments in the field of transnational organised crime under international law. It traces the history of organised crime and explores key concepts and norms relating to the practice from a multi-disciplinary perspective. It looks at legal obligations imposed upon States.